Hepatitis B and C Virus Infection in Patients with Non-Hodgkin Malignant Lymphoma: Prevalence, Clinical, Biological, Evolution and Therapeutic Particular Features - Tőrők-Vistai, Tünde; Petrov, Ljubomir (Medicine and Pharmacy Reports, 2014)
Objectives. Investigating the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) in B-cell non-Hodgkin’s lymphoma (B-NHL) patients and identification of clinical, biological, evolutive and therapeutic features of viral infection-associated lymphomas. Methods. We retrospectively studied 200 patients with B-NHL, screened for hepatitis viruses and treated at the Hematology Clinic Cluj-Napoca. We identified and characterised those who tested positive. Demographic, clinical, biological and therapeutic datas were analyzed. Prevalence of HBV and HCV infection was compared with data reported by the Blood Transfusion Center Cluj-Napoca and data from the literature. For statistical analysis the chi-square and Fisher tests were used. Results. The prevalence of hepatitis viruses in B-NHL patients was 15% for HBV, 20% for HCV and 3% for double HBV+HCV infection, significantly higher then in the general population. Severe hepatocytolisis after chemotherapy was more frequent in agressive lymphomas associated with HBV infection. Changing of the planned chemotherapy was seen in 24% of the patients. The incidence of hepatocytolisis and of chemotherapy changes were lower in patients who received antiviral therapy. Conclusions. High prevalence of HBV and HCV infection in B-NHL patients proves their role in lymphomagenesis. The addition of antiviral treatment to chemotherapy can prevent severe hepatitis and treatment modifications. Virological screening is mandatory in order to prevent these complications.